2001
DOI: 10.1590/s0100-879x2001000800007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 17ß-estradiol or alendronate on the bone densitometry, bone histomorphometry and bone metabolism of ovariectomized rats

Abstract: The objective of the present study was to evaluate the effect of 17ß-estradiol or alendronate in preventing bone loss in 3-month-old ovariectomized Wistar rats. One group underwent sham ovariectomy (control, N = 10), and the remaining three underwent double ovariectomy. One ovariectomized group did not receive any treatment (OVX, N = 12). A second received subcutaneous 17ß-estradiol at a dose of 30 µg/ kg for 6 weeks (OVX-E, N = 11) and a third, subcutaneous alendronate at a dose of 0.1 mg/kg for 6 weeks (OVX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
0
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 36 publications
10
26
0
7
Order By: Relevance
“…Elevated plasma osteocalcin levels following ovariectomy have been reported in previous studies [7][8][9][10] A similar finding was observed in the present study in the Ovx group; however, the alendronate group showed no change in the plasma osteocalcin levels, compared to the Shm group. This finding supports the bone loss in the Ovx group without alendronate supplementation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Elevated plasma osteocalcin levels following ovariectomy have been reported in previous studies [7][8][9][10] A similar finding was observed in the present study in the Ovx group; however, the alendronate group showed no change in the plasma osteocalcin levels, compared to the Shm group. This finding supports the bone loss in the Ovx group without alendronate supplementation.…”
Section: Discussionsupporting
confidence: 92%
“…Due to increased life span and the use of more sophisticated diagnostic techniques. The high rate of bone loss in the Ovx rats has been shown to be preventable using similar postmenopausal treatment regimens as in humans [7][8][9][10] As a result, the Ovx rat model is recognized as the gold standard in studies which aim to prevent and slow down osteoporosis in humans. In the present study, we developed an osteoporotic rat model to assess the effects of postmenopausal osteoporosis on trabecular bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Para a confecção do aparelho gessado, os animais foram anestesiados por via intraperitoneal com xylazina 20% (Rompun ® , Bayer) 12mg/ kg e ketamina 10% (Ketalar ® , Parke-Davis) 95mg/kg, como descrito por outros autores (19,23) . Com o animal anestesiado, a região a ser imobilizada foi envolvida por malha tubular e ataduras de algodão.…”
Section: Este Estudo Foi Conduzido De Acordo Com O Guide For the Careunclassified
“…As doses utilizadas foram de 0,7mg/ kg aplicadas subcutaneamente no dorso, uma vez por semana, durante 28 dias (12,19) . Os animais foram mortos por meio de dose excessiva de tiopental sódico (Thionembutal ® ) administrado intraperitonealmente.…”
Section: Este Estudo Foi Conduzido De Acordo Com O Guide For the Careunclassified
See 1 more Smart Citation